Identificación de portadores de Salmonella spp., mediante coprocultivo en adjudicatarios del mercado “Reina del cisne” de la ciudad de Loja - Aguilar Quizhpe, Karen Dayana (2023)
The infection produced by Salmonella or also called salmonellosis is caused by inadequate hygienic handling of food associated mainly with vegetables, fruits, animal products such as milk, shellfish, meat and raw eggs, as well as the intake of contaminated water; the invasion produced by the pathogen tends to affect the intestinal tract causing vomiting, recurrent diarrhea, abdominal pain and high fever. Faced with infection by the microorganism, there are people who do not present any type of manifestations or clinical pictures of the disease, however, it can be transmitted once the chronic carrier condition has developed, a state that allows the microorganism to lodge in the gallbladder causing its dissemination in a prolonged and recurrent manner. The study population of the present investigation was made up of awardees and employees of the food stalls of the supply center, where 60 biological samples of people who decided to participate in the project were analyzed, which was developed with the objective of identifying carriers of Salmonella spp., in awardees and employees of the food stalls of the “Reina del Cisne” de la ciudad de Loja market using coproculture in selective salmonella-shigella (SS) media as a microbiological method and implementing biochemical tests in order to identify the type of species isolated. The analysis carried out determined that of the total number of isolated samples, 6 presented growth of colonies with characteristics typical of the bacterium, in turn, the biochemical tests allowed the isolation of 2 species of Salmonella Typhi and 4 of Salmonella spp